Successful implantation of a Coronary stent graft in a peripheral vessel - Heß, Alexander; Heilmeier, Britta; Kohler, Benedikt; Müller, Oliver J.; Katus, Hugo; Korosoglou, Grigorios (Case reports in vascular medicine, 2015)
Peripheral artery disease (PAD) is a complex, often underdiagnosed illness with rising prevalence in western world countries. During the past decade there has been a rapid advance especially in the field of endovascular treatment of PAD. Here we present for the first time a case reporting on the placement of coronary stent graft in a peripheral vessel for the management of a peripheral side branch perforation. Interventional angiologists or radiologists may consider such an option for complication management after injury of smaller vessels during peripheral percutaneous interventions. Further specialization and novel options of complication management as described in our case may shift the treatment from surgical to even more endovascular treatment procedures in the future.
Gesehen am 31.08.2020